Association between megakaryocyte abnormalities on bone marrow smear and response to thrombopoietin receptor agonists in adult patients with primary immune thrombocytopenia. (17th November 2022) - Walter, Ondine; Ribes, Agnès; Germain, Johanne; Rieu, Jean-Baptiste; Comont, Thibaut; Plat, Albertine; Rivière, Brigitte; Deluche, Laureline; Delarue, Lucrecia; LeGoff, Isabelle; Greze, Monique; Dubourdieu, Béatrice; et al.
Abstract: Impaired platelet production is a mechanism of immune thrombocytopenia (ITP). Morphological abnormalities of megakaryocytes (MKs) are sometimes observed in this disease. Two studies have suggested an association between MK abnormalities and response to corticosteroids in primary ITP, but none have investigated this association for thrombopoietin-receptor agonists (TPO-RAs). This was the aim of this study. The source of population was the French CARMEN registry with prospective follow-up of adult patients with incident ITP. We included patients with primary ITP, treated by TPO-RA and with a bone marrow smear before initiating TPO-RA. MK abnormalities were categorized by the presence of dysplasia and by the stage of maturation. Among 451 patients screened, 38 were included in the analysis. There was no difference in the median percentage of dysplastic MKs between responders to TPO-RA (4.0%, 95% confidence interval – CI: 2.3–6.4) and non-responders (4.5%, 95% CI: 0.7–7.1). There was a slightly higher proportion of granular MKs (4.5%, 95% CI: 3–6) and basophilic MKs (30.1%, 95% CI: 21.9–39.1) in non-responders compared to responders (granular: 2.0%, 95% CI: 0–4.1; basophilic: 21.3%, 95% CI: 11.4–40.7). In conclusion, MK abnormalities were not associated with response achievement in ITP patients treated with TPO-RA in this series of 38 patients.